2023
DOI: 10.3390/vaccines11091432
|View full text |Cite
|
Sign up to set email alerts
|

Mpox Vaccination Hesitancy and Its Associated Factors among Men Who Have Sex with Men in China: A National Observational Study

Min Zheng,
Min Du,
Guanghong Yang
et al.

Abstract: More than 400 confirmed mpox cases have been reported in China. The mpox vaccination is crucial to mitigate mpox transmission, especially for at-risk populations. This study aimed to determine mpox vaccination hesitancy and its associated factors in Chinese men who have sex with men (MSM). This nationwide cross-sectional study was conducted among 7538 Chinese MSM in 27 MSM social organizations from 21 provinces, municipalities, and autonomous regions of China from 31 July to 4 August 2023. Of them, the rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…In addition, vaccines remain essential in disease prevention and control as an effective means of protection. Similar to previous research on mpox vaccine among MSM,56 we found that patients also expressed a strong desire for vaccines. This underscores the urgency of accelerating the introduction and development of vaccines.Our study has several limitations.…”
supporting
confidence: 89%
“…In addition, vaccines remain essential in disease prevention and control as an effective means of protection. Similar to previous research on mpox vaccine among MSM,56 we found that patients also expressed a strong desire for vaccines. This underscores the urgency of accelerating the introduction and development of vaccines.Our study has several limitations.…”
supporting
confidence: 89%
“…All participants were recruited and guided by training health staffs to confirm the accurate selection of participants and the completion of the questionnaire. The distribution of MSM social organizations is seen in Table 22 . Briefly, after excluded female respondents, we recruited participants who provided informed consent, identified as gay or bisexual, aged ≥18 years old, self‐reported having sex with at least one man in the past 12 months (anal sex, oral sex, hand sex, hugging, touching, kissing, etc.)…”
Section: Methodsmentioning
confidence: 99%
“…The distribution of MSM social organizations is seen in Table S1. 22 Briefly, after excluded female respondents, we recruited participants who provided informed consent, identified as gay or bisexual, aged ≥18 years old, self-reported having sex with at least one man in the past 12 months (anal sex, oral sex, hand sex, hugging, touching, kissing, etc.) and lived in mainland, China.…”
Section: Data Sourcementioning
confidence: 99%
“…The details were described in our previous study. 20 We recruited MSM who were at least 18 years old and reported engaging in sexual activities with at least one man in the past 12 months (including anal sex, oral sex, hand sex, hugging, touching, kissing, etc.) in mainland China.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we analyzed the factors that influenced mpox vaccination in PLWH and PLWoH. 20 However, we did not analyze the association between HIV status and hesitation toward mpox vaccination. PLWH may face greater challenges in receiving the mpox vaccine due to concerns about the safety of the vaccine in immunocompromised populations.…”
Section: Introductionmentioning
confidence: 99%